Constitutional Identity and Relations Between the European Union Law and the Hungarian Law - Varga, András Zs.; Berkes, Lilla (Common Values and Constitutional Identities: Can Separate Gears Be Synchronised?, 2023)
In its Decision 22/2016. (XII. 5.), the Constitutional Court set several limits on the implementation of European Union (EU) acts that go beyond the scope of conferred or jointly exercised powers. The Constitutional Court has stated that, based on a motion to that effect, it could examine whether the joint exercise of powers infringes on human dignity and other fundamental rights or Hungary’s sovereignty and identity based on its historical constitution. The decision introduced a new, previously unknown limit to the exercise of shared competence in constitutional dialogue by formulating the term constitutional identity.The legal nature of Hungary’s constitutional identity is the specificity of the communities that make up the state and nation, which does not apply to other nations in the same way or at all. In Hungary, national identity is inseparable from constitutional identity. The fundamental values that constitute identity have been established through the historical development of the Constitution, and the nation has always adhered to them. The values that constitute a country’s identity are legal facts that cannot be renounced by either an international treaty or an amendment to Fundamental Law. The latest addition to the constitutional dialogue is Decision 32/2021 (XII. 20.). Its significance lies in the fact that the Constitutional Court was not reluctant to use the Ultravires argument against EU acts adopted in the absence of the unions’ competence. In connection with this, this study provides an overview of the relationship between the EU and Hungarian law through the practice of the Constitutional Court. The chapters cover the constitutional issues of the incorporation of EU Law, its emergence in the practice of the Constitutional Court, and the various approaches, from staying away to developing control and emphasising constitutional dialogue as a means of avoiding conflict. Keywords: constitutional identity, Constitutional Court of Hungary, sovereignty, EU law, ultra vires